Today is the day you change your life - Harrison, Elaine , 1963- (Pearson, 2011)
"If you're restless, dissatisfied,irritable,indecisive, unhappy or just feel like there's something missing, then you're ready for change - and this is the book for you. Whether you know what it is that you need to tackle, or whether you need help to work out what you want (and what you don't want), you can change your life for the better, starting today. And when the way forward is broken down into small, simple steps, it can be far less daunting than you might think. It feels amazingly good to start doing something about your situation. What's more, it's liberating and life enhancing to find yourself back in charge. Sometimes it's just a matter of knowing where to start and when. So how about right here, right now?"